Analytical Approaches for Addressing The Variation in Back-Calculated Age-Length Relationships for Fish - Samuel Shephard; Donald C Jackson (Tropical Life Sciences Research, 2009)
Estimating an age-length relationship is a routine aspect of many fisheries studies and is simplified by the use of commercially available computer programs. These computer programs may be misleading since a result can be produced irrespective of the quality or the extent of the data, and there is some concern that back-calculated agelength relationships are sensitive to the sample size and composition. We investigated this issue by comparing estimates of mean back-calculated lengths at age and growth rates derived from subsets of a large sample of wild channel catfish Ictalurus punctatus (N=788) collected in 2001 and 2002 from 9 rivers in Mississippi, United States. Estimates of growth rate varied among subsets consisting of individual year class (2–6) of channel catfish separated from the overall sample. For nine subsets, comprising randomly-selected and increasing proportions of the overall sample (20%–100% at 10% increments of the overall sample), growth was similar. However, growth differed for a subset representing a random 10% of the overall sample. Lengths at age and growth rates derived from each of the 2001 and 2002 components of the sample both differed. All results were significant at P < 0.05. Menganggar pertalian di antara umur dan panjang ikan merupakan suatu aspek rutin dalam banyak kajian perikanan dan ianya telah dipermudahkan dengan penggunaan program komputer komersil. Program-program ini boleh mengelirukan memandangkan suatu keputusan boleh dihasilkan tanpa mengambil kira kualiti dan jumlah data, dan juga terdapat sedikit kebimbangan mengenai pertalian umur dan panjang ikan yang dikira secara kebelakang (back calculated) yang sensitif kepada saiz dan komposisi sampel. Kami telah menyelidik isu ini dengan membandingkan anggaran purata umur dan kadar tumbesaran ikan channel catfish Ictalurus punctalus liar (N=788) yang telah dikira secara kebelakang. Sampel tersebut telah diambil daripada beberapa subset dalam satu sampel yang besar yang telah diambil pada tahun 2001 dan 2002 dari 9 sungai di Mississippi, United States. Anggaran kadar tumbesaran adalah berbeza daripada kadar tumbesaran purata untuk sampel keseluruhan. Kadar tumbesaran adalah sama bagi subset-subset rawak daripada jumlah sampel keseluruhan (20%–100% dalam peningkatan 10%) tetapi berbeza bagi sub-sampel 10%. Kedua-dua panjang ikan mengikut umur dan kadar tumbesaran daripada komponen sampel 2001 dan 2002 adalah berbeza. Semua keputusan adalah signifikan pada P < 0.05.